Testing models of thorium and particle cycling in the ocean using data from station GT11-22 of the U.S. GEOTRACES North Atlantic section. (July 2016) - Lerner, Paul; Marchal, Olivier; Lam, Phoebe J.; Anderson, Robert F.; Buesseler, Ken; Charette, Matthew A.; Edwards, R. Lawrence; Hayes, Christopher T.; Huang, Kuo-Fang; Lu, Yanbin; Robinson, Laura F.; Solow, Andrew
Abstract: Thorium is a highly particle-reactive element that possesses different measurable radio-isotopes in seawater, with well-constrained production rates and very distinct half-lives. As a result, Th has emerged as a key tracer for the cycling of marine particles and of their chemical constituents, including particulate organic carbon. Here two different versions of a model of Th and particle cycling in the ocean are tested using an unprecedented data set from station GT11-22 of the U.S. GEOTRACES North Atlantic Section: (i) 228, 230, 234 Th activities of dissolved and particulate fractions, (ii) 228 Ra activities, (iii) 234, 238 U activities estimated from salinity data and an assumed 234 U/ 238 U ratio, and (iv) particle concentrations, below a depth of 125 m. The two model versions assume a single class of particles but rely on different assumptions about the rate parameters for sorption reactions and particle processes: a first version (V1) assumes vertically uniform parameters (a popular description), whereas the second (V2) does not. Both versions are tested by fitting to the GT11-22 data using generalized nonlinear least squares and by analyzing residuals normalized to the data errors. We find that model V2 displays a significantly better fit to the data than model V1. Thus, the mere allowance of vertical variations in the rate parameters can lead to a significantly better fit to the data, without the need to modify the structure or add any new processes to the model. To understand how the better fit is achieved we consider two parameters, K = k 1 / ( k − 1 + β − 1 ) and K / P, where k 1 is the adsorption rate constant, k −1 the desorption rate constant, β −1 the remineralization rate constant, and P the particle concentration. We find that the rate constant ratio K is large ( ⩾ 0.2 ) in the upper 1000 m and decreases to a nearly uniform value of ca. 0.12 below 2000 m, implying that the specific rate at which Th attaches to particles relative to that at which it is released from particles is higher in the upper ocean than in the deep ocean. In contrast, K/P increases with depth below 500 m. The parameters K and K/P display significant positive and negative monotonic relationship with P, respectively, which is collectively consistent with a particle concentration effect. Abstract : Highlights: Two versions of a thorium and particle cycling model are fit to data from station GT11-22 of the U.S. GEOTRACES North Atlantic Section using an inverse method. Model V2 with depth-dependent rate parameters fits the data better than model V1 with uniform rate parameters. We find that deviations in Th profiles from those predicted from reversible exchange are at least partly explained by vertical variations in the rate constants. We find evidence of a particle concentration effect at this station.